2021
DOI: 10.1111/ijcp.14683
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus colonisation, prevalence, associated risk factors and antimicrobial susceptibility pattern among pregnant women attending antenatal care at Dschang District Hospital, West Region of Cameroon: A hospital‐based cross‐sectional study

Abstract: Background: Group B Streptococcus (GBS), also known as Streptococcus agalactiae, is a Gram-positive bacterium known for its ability to colonise the vaginal and rectal areas of the mother and is a leading cause of neonatal mortality and morbidity. This study aimed at determining the prevalence, associated risk factors and antimicrobial susceptibility of GBS colonisation among pregnant women attending antenatal care (ANC) at Dschang District Hospital. Methods:This hospital-based cross-sectional study used a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(37 reference statements)
3
3
0
Order By: Relevance
“…Of the independent variables that were assessed, history of premature birth, history of preterm delivery, and history of premature rupture of the membrane were statistically significantly associated with the prevalence of GBS. In the present study, a history of stillbirth was statistically significantly associated with the prevalence of GBS, which was in agreement with the studies reported from Cameroon 43 and Ethiopia. 31 Several findings indicate that GBS infection during pregnancy can result in issues such as premature membrane rupture, stillbirth, and preterm delivery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of the independent variables that were assessed, history of premature birth, history of preterm delivery, and history of premature rupture of the membrane were statistically significantly associated with the prevalence of GBS. In the present study, a history of stillbirth was statistically significantly associated with the prevalence of GBS, which was in agreement with the studies reported from Cameroon 43 and Ethiopia. 31 Several findings indicate that GBS infection during pregnancy can result in issues such as premature membrane rupture, stillbirth, and preterm delivery.…”
Section: Discussionsupporting
confidence: 93%
“…2,14,26,31,[39][40][41] In contrast to the present finding, a low prevalence of GBS was reported in Tigray (11.3%), Addis Ababa (7.3%), Cameroon (8.69%), Burkina Faso (6.05%), Iraq (6.7%), and China (3.5-8.7%). 8,18,[42][43][44][45] These results indicate that the prevalence of maternal GBS colonization, which is the primary risk factor for the early onset of GBS disease, differs in different countries and within the same country. 11 The variation might be due to the sample size variation, the gestational period of participants, or geographical location.…”
Section: Discussionmentioning
confidence: 99%
“…Bivariate analysis revealed no association of anemia (Hb < 110 g/L), parity, gravidity, gestational age, delivery method, preterm birth, birth weight, fetal sex, and gestation age for GBS screening with GBS colonization in late pregnancy ( P > 0.05) while maternal age, gestational week of birth, and PROM were correlated with GBS colonization ( P < 0.05). The lack of association of parity, gravidity, delivery method, birth weight, and fetal sex with maternal late GBS colonization was consistent with previous findings; however, data were inconsistent regarding maternal age, anemia, preterm birth, diabetes, and PROM [ 3 , 8 , 13 , 18 , 28 , 29 ]. These discrepancies may be attributable to differences in demographics, sexual activity during pregnancy, cutoff points, and fitted model structures [ 1 , 8 ].…”
Section: Discussionsupporting
confidence: 89%
“…Group B Streptococcus (GBS), also known as Streptococcus agalactiae, is a gram-positive bacterium with the ability to transfer infection from mother to fetus, causing neonatal sepsis and meningitis [1][2][3]. e latest worldwide systematic review disclosed rates of GBS colonization in pregnant women ranging from 2.0 to 32.0% [4].…”
Section: Introductionmentioning
confidence: 99%
“…This nding was relatively comparable to reports from Addis Ababa (14.6%) (Assefa et al, 2018), Hawassa (15.7%) (Ali et al, 2019), and Brazil (14%) (Siqueira et al, 2019). Whereas it was greater than the study ndings in Southern Asia (12.5%) and Eastern Asia (11%) (Russell et al, 2017a), Iran (11.8%) (Darabi et al, 2017), Yemeni, (10.95%) (AL-Subol et al, 2021), Cameroon (8.69%) (Sama et al, 2021), Namibia (13.6%) (Mukesi et al, 2019), Adama, Ethiopia (13.2%) (Ali et al, 2020), Arbaminch, Ethiopia (8.5%) (Shiferawu et al, 2019), Eastern, Ethiopia (13.68%) (Yadeta et al, 2018b), and in Nekemte, Ethiopia (12.2%) (Mengist et al, 2017).…”
Section: Discussionsupporting
confidence: 70%